2020
DOI: 10.14744/hnhj.2020.27928
|View full text |Cite
|
Sign up to set email alerts
|

Depression, social phobia and quality of life after major lower limb amputation

Abstract: Introduction: In this study, we aimed to compare the social phobia, depression and quality of life in patients with major lower limb amputation to non-amputated. Methods: Patients who were underwent above or below the knee amputation in the past were evaluated retrospectively by examining the hospital records. All the participants were administered Liebowitz Social Anxiety Scale (LSAS), Hospital Anxiety and Depression Scale (HADS), and Short-Form 36 (SF-36). Results: The number of patients was 30 (21 males, ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Regarding the impact of the amputation level on anxiety and depression, the study showed that amputation at the trans-femoral level presents a greater risk of having anxiety symptoms and depression than at the transtibial level. This result agrees with the study of Tutak et al [ 11 ]. In this sense, an Iranian study carried out on veterans who had undergone a unilateral transfemoral amputation showed that depression (32% confirmed depressed and 26% suspected) and anxiety (31% confirmed and 28% suspected) have a high prevalence among participants [ 29 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Regarding the impact of the amputation level on anxiety and depression, the study showed that amputation at the trans-femoral level presents a greater risk of having anxiety symptoms and depression than at the transtibial level. This result agrees with the study of Tutak et al [ 11 ]. In this sense, an Iranian study carried out on veterans who had undergone a unilateral transfemoral amputation showed that depression (32% confirmed depressed and 26% suspected) and anxiety (31% confirmed and 28% suspected) have a high prevalence among participants [ 29 ].…”
Section: Discussionsupporting
confidence: 94%
“…However, a Brazilian study reported a prevalence of around 68.5% [ 24 ]. In general, the prevalence of symptoms of anxiety and depression after MLLA gradually decreases, whether at three months [ 18 ], six months [ 21 ], or one year and more [ 11 , 14 , 21 , 25 - 27 ]. This reduction can be explained by the relief of pain, and the absence of fear and worry after the MLLA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations